2021
DOI: 10.3390/app11041940
|View full text |Cite
|
Sign up to set email alerts
|

Age of Information and Success Probability Analysis in Hybrid Spectrum Access-Based Massive Cognitive Radio Networks

Abstract: In this paper, we investigate users’ performance under the hybrid spectrum access model in the massive cognitive radio network (CRN), where multiple primary users (PUs) and secondary users (SUs) transmit on the same channel simultaneously. SUs first detect the state of the channel via channel sensing and select an appropriate channel access scheme (either underlay or overlay) for their transmissions based on the outcome of the channel sensing. When at least one PU is active, SUs transmit under the underlay cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We now numerically analyze the performance of the multilayer edge computing system investigated in this paper and validate the analyses using independent Monte Carlo simulations averaged over 50, 000 channel realizations. Except otherwise stated, the following simulation parameters were used similar to [11], [12], [45]…”
Section: Numerical Simulations and Resultsmentioning
confidence: 99%
“…We now numerically analyze the performance of the multilayer edge computing system investigated in this paper and validate the analyses using independent Monte Carlo simulations averaged over 50, 000 channel realizations. Except otherwise stated, the following simulation parameters were used similar to [11], [12], [45]…”
Section: Numerical Simulations and Resultsmentioning
confidence: 99%
“…It was also observed that a greater spectral efficiency does not directly translate into a lower average AoI. Another scenario that includes power control to simplify the reception of the intermittent packets was studied in [19], which derived analytical formulas for throughput and AoI with those settings.…”
Section: Related Workmentioning
confidence: 99%